Progressive encephalomyelitis with rigidity: a Taiwanese case and review of literature - Chang, A; Lin, K-Y; Chuang, K-J; Waters, P; Irani, SR; Mgbachi, V; Yeh, H-L; Lien, L-M; Chiu, H-C; Chen, W-H (Elsevier, 2021)
Introduction Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a rare disorder. However, the outcome is still variable with different serological and tumor associations, and the elements to good response with less relapse is yet to be elucidated. Method We present a case and obtain a literature review of patients with PERM and make comparisons based on different serological groups. We also analyze patients with idiopathic PERM that had detailed medical records. Results 81 patients were collected and analyzed. The largest group were glycine receptor-antibody (GlyR-Ab)-positive (70%), and the seropositive-GlyR-Ab-negative group had better response to immunotherapy. Malignancy can occur up to 2 years from the presentation of PERM. Among the 18 cases with detailed records, the patients who had good outcome initiate immunotherapy within 2 months from presentation. 9 of the 12 patients who experienced no relapse had non-steroid immunotherapy. The maximal interval time of relapse was 24 months. Conclusion We recommend tumor surveillance up to 2 years in patients with PERM and early administration of immunotherapies and maintain with non-steroid immunotherapy with or without oral corticosteroid for a minimum of 2 years to reduce the risk of relapse in GlyR-Ab-positive patients.